Memerkarakan Identitas Nasional: Representasi Identitas Kultural dalam Sinema Generasi Baru Indonesia dan Malaysia - Irawanto, Budi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2008)
Cinema has been long seen as a trans-cultural phenomenon due to its cross-cultural ability. Cinema posits itself to entertain and to educate people from various backgrounds by using its